Perbaikan Skala Usaha Sapi Potong Pada Kelompok Peternak Malingping Dan Hasanah Di Kabupaten Sukabumi - Supardi Rusdiana; L. Praharani; D.A. Kusumaningrum (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
The purpose of this study was to determine the improvement of beef cattle business scale in Mmalingping and Hasanah breeders in Sukabumi Regency. The study was conducted on a group of beef cattle farmers in Purabaya District, Sukabumi Regency, West Java Province, in 2016. With a structured interview survey method for a group of Malingping beef cattle breeders by purposive random sampling as many as 18 farmers, and the Hasanah breeders group of 18 farmers. Each group of breeders is divided into 2 (two) parts, namely group I maintains beef cattle on a 2-3-scale scale and group II maintains beef cattle on a scale of 4-6 head. The research data is then tabulated by descriptive, quantitative and financial economic analysis of the B/C ratio. The results of the financial economic analysis of the net profit in the breeders of Malingping  beef  cattle  from  the  maintenance  of  2  mains  to  3  mains  of  IDR 2,078,000/year to IDR 5,799,500/years, or an increase of 65.13%, B/C ratio 1.06-1.12. The net profit in the Hasanah beef cattle breeders group from 2 parent scale maintenance to 3 parent head scale is IDR 2,384,000/year to be IDR 5,009,250/year, or an increase of 64.18%, B/C ratio 1.05-1.10. If the Malingping and Hasanah beef cattle  breeders  maintain  a  scale  of  >3  productive  female  mothers,  it  is  veryeconomical, effective and efficient, economically beneficial.